MANIPULATION OF THE BODIES: AN IMPERIALISM ALSO IN THE PHYSICAL EDUCATION (Fiep Bulletin - online, 2014)
The objective of this work was to explicit of critical form the necessity created for the society, of the citizens to have that to develop a body standard, manipulated and manipulability, from the perspective of different authors and to search and to understand as the Physical Education comes dealing with this ideal of body throughout the time, leading in account this historical form of "corporal instrumentalization". To arrive at this end the used methodology it was the literature revision. To the end of this work it could be concluded that the bodies see suffering manipulation have very, and into the current times this manipulation if transforms into an obsession for a perfect body, stimulating the consumption indirectly to get this body; and the Physical Education is not other people's to this, unhappily at some moments it had even though a crucial paper so that this instrumentalization of the body occurred.
Keywords: bodies; manipulation; Physical Education